Catalysis with Gold Complexes Immobilised on Carbon Nanotubes by π–π Stacking Interactions: Heterogeneous Catalysis versus the Boomerang Effect. Issue 36 (16th July 2013) - Vriamont, Charles; Devillers, Michel; Riant, Olivier; Hermans, Sophie
Abstract A new pyrene‐tagged gold(I) complex has been synthesised and tested as a homogeneous catalyst. First, a simple 1, 6‐enyne was chosen as a model substrate for cyclisation by using different solvents to optimise the reaction conditions. The non‐covalent immobilisation of our pyrene‐tagged gold complex onto multi‐walled carbon nanotubes through π–π stacking interactions was then explored to obtain a supported homogeneous catalyst. The heterogenised catalyst and its homogeneous counterpart exhibited similar activity in a range of enyne cyclisation reactions. Bearing in mind that π–π interactions are affected by temperature and solvent polarity, the reuse and robustness of the supported homogeneous catalyst was tested to explore the scope and limitations of the recyclability of this catalyst. Under the optimised conditions, recyclability was observed by using the concept of the boomerang effect.